Fine-needle aspiration with rapid parathyroid hormone assay to identify parathyroid gland in thyroidectomy - Zou, Xian (Medicine (Baltimore), 2020)
To determine the levels of parathyroid hormone (PTH) in the fluids of various tissues for identification of parathyroid glands during thyroidectomy. Our study comprised 31 patients with thyroid cancer who underwent lobectomy with central compartment dissection at our hospital from October 2014 to February 2015. A total of 186 tissue samples, including 28 from parathyroid glands and 158 from non-parathyroid tissues, were obtained during the operations. Tissue fluids were collected via fine-needle aspiration to measure PTH levels; the tissue was punctured 3 times with a 26-gauge syringe needle and washed with 0.5 mL normal saline. Tissues were also prepared for pathological examination. PTH concentrations were significantly higher in parathyroid tissues than non-parathyroid tissues. None of the patients had irremediable parathyroid dysfunction after surgical resection. Use of fine-needle aspiration for quantification of PTH levels in tissue fluids rapidly, safely, and effectively identifies the parathyroid glands during thyroidectomy.